2019
DOI: 10.1016/j.foodhyd.2019.105184
|View full text |Cite
|
Sign up to set email alerts
|

The influence of charge on the multiple thermal transitions observed in xanthan

Abstract:  Transitions in xanthan with charged pyruvate groups occur at lower temperatures  A mass action model describes changes in transition temperature with salt addition  Xanthans having biphasic transitions have phases with different levels of pyruvate  Salt differentially affects transition temperatures of different pyruvate phases  A linear relation exists between ln[NaCl] and the reciprocal transition temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…These findings arise from xanthan, which is characterized by high molecular mass and the formation of ordered structures with a high shear‐thinning flow behavior. It provides solutions of high viscosity and the formation of stiff, rod‐like molecules stabilized by their side chains, which consist of mannoses and glucuronic acids (Abbaszadeh et al., 2019; Morris, 2019). In Table 1, it is observed that from 0.1% xanthan concentration, in mixtures with 5% AF, k values present significant differences compared to the lowest concentrations of xanthan used (0.03% and 0.05%) ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings arise from xanthan, which is characterized by high molecular mass and the formation of ordered structures with a high shear‐thinning flow behavior. It provides solutions of high viscosity and the formation of stiff, rod‐like molecules stabilized by their side chains, which consist of mannoses and glucuronic acids (Abbaszadeh et al., 2019; Morris, 2019). In Table 1, it is observed that from 0.1% xanthan concentration, in mixtures with 5% AF, k values present significant differences compared to the lowest concentrations of xanthan used (0.03% and 0.05%) ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…With the addition of AF to xanthan solutions, a decrease in k values and an increase in n values were observed as the AF content was increased in the AF–xanthan 0.03% mixtures; the exception was the mixture with 5% AF concentration, whose values did not present significant differences with those of the mixture with 3% AF ( p > 0.05); yield stress was not detected. These trends could be attributed to AF interference in the xanthan molecule association since AF has hydroxyl groups on carbons 3, 4, and 6 of each fructose unit (Ignot‐Gutiérrez et al., 2020), which can form hydrogen bonds with the negatively charged groups on xanthan, justified on the basis that the negatively charged groups are located at the outside of the helical structure of xanthan (Abbaszadeh et al., 2019; Long y et al., 2013), as well as that the AF charge is weak, being in the range of units (Sosa‐Herrera et al., 2016). Mixtures of AF–xanthan 0.03% and SC 1% showed lower k values than the samples without SC.…”
Section: Resultsmentioning
confidence: 99%
“…The salt presence increases the transition temperature by reducing the effective charge of the xanthan chains. A linear relationship between the natural logarithm of the salt concentration and the reciprocal temperature was observed [180].…”
Section: Xanthan Gummentioning
confidence: 93%